PENGANGKUTAN KAYU ULIN (Eusideroxylon zwageri T.&B.) MENGGUNAKAN SEPEDA MOTOR (OJEK ULIN) DARI WILAYAH KECAMATAN KINTAP - Dimas Zulfian Nugroho; Suyanto Suyanto; Rina Kanti (Universitas Lambung Mangkurat, 2020)
Liang Anggang and surrounding areas, Ironwood needs are mostly fulfilled from the Kintap area and its surroundings. The local government has tried to preserve Ulin by making regional regulations regarding the load of ironwood. Tanah Laut Regency with Regional Regulation No. 35 of 2005 has banned transporting Ironwood uses four-wheeled vehicles and allows two-wheeled vehicles to carry the longest 1.5m Ironwood arrears known as Ironwoodmotorcycle. This study aims to find out information about the load of Ironwood from the Kintap Subdistrict area and its surroundings to the Liang Anggang area, namely from aspects: background, transportation equipment, socio-economic dimensions of wood, timber volume and income. The benefit of this research is to be able to provide information about transporting Ironwood to the relevant Service as a basis for consideration in formulating a policy relating to the existence of ulin motorcycle. The object in this study was ironwood motorcycle who crossed the streets of banjarmasin province. The data obtained consisted of 2 types of data, namely primary data obtained by direct interviews with ironwood motorcycle, along with related parties, and secondary data obtained by collecting data from relevant agencies. The results show that if assumed to be the same condition as the number of Ironwood motorcycle and Ironwood supplies from the Kintap area, then since 2005 the average number of Ironwood transported to the Anggang Liang area is around 105,330.50 m3 / 12 years.Keywords: Motorcycle ulin wood; Ironwood